Harlequin Ichthyosis : A Rare Congenital Entity (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Harlequin Ichthyosis (HI) is an extremely rare genetic skin disorder. It is the most severe type of ichthyosis. It is characterized by thickened, dry, rough and armor like plates of skin with deep cracks in between.  Alternative names for HI include- keratosis diffusafetalis, ichthyosis congenital, ichthyosis fetalis, harlequin fetus and ichthyosis congenital gravior. It is an autosomal recessive disorder with the majority of affected individuals being homozygous for mutation in the ABCA 12 gene. This condition presents with a wide range of severity and symptoms. Affected neonates usually do not survive beyond first few days of life. We are presenting prenatal diagnosis of a case of this rare condition.  Bangladesh J Obstet Gynaecol, 2023; Vol. 38(1): 49-52